Competitive Advantage of Operational and Dynamic Information Technology Capabilities - Bullon, Luis A. (2009)
Based on contradictory findings reported by researchers into the payoffs of information technology (IT) investments, a key question for information system researchers and practitioners concerns what role IT may play in enhancing competitive advantage. In this study, IT is conceptualized as a capability, and a differentiation is made between the routine use of IT as operational IT capability and the purposeful use of IT to achieve change, that is, dynamic IT capability, in order to analyze and describe the direct effect of IT capabilities on competitive advantage. The research design will be a cross-sectional survey, using structural equation modeling (SEM), and the empirical analysis will take as its population the financial and industrial firms of Lima, Peru.